Kinerja Usaha dan Optimasi Laba Agribisnis Lele Gelondongan pada Sistem Kolam Penampungan - Purnomo, Fajar; Muawanah (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2024)
The catfish fingerling agribusiness offers a more promising prospect compared to catfish seed production or grow-out farming. At the production level, the use of probiotics significantly influences the Survival Rate (SR), Feed Conversion Ratio (FCR), and biomass. Although the technical performance shows favorable results, economic efficiency is not necessarily guaranteed, as a business is considered efficient only when the utilization of resources produces output that exceeds the input. This study aims to analyze business performance and measure the economic efficiency of the catfish fingerling agribusiness in pond holding systems. The rearing process was conducted for one week using ponds measuring 2.5 × 2.5 × 0.5 meters. Feed consisted of natural feed—boiled chicken intestines and shrimp shells—and fermented pellet feed, administered at 100 g per fish per week. The results showed an SR ranging from 98.6% to 100%, an FCR between 0.83 and 0.95, and biomass gains of 14.4–21 kg. Revenue per holding pond ranged from IDR 170,325 to IDR 271,925, with the highest Revenue/Cost Ratio (R/C) of 1.265 recorded in pond D and the lowest of 1.198 in pond C. These findings indicate that while technical performance is high, variations in economic efficiency persist across ponds, suggesting that feed management and maintenance practices must be optimized to maximize profitability.